2011
DOI: 10.2134/agronj2010.0404
|View full text |Cite
|
Sign up to set email alerts
|

Response of Green Peach Aphids and Other Arthropods to Garlic Intercropped with Tobacco

Abstract: The green peach aphid, Myzus persicae (Sulzer), is an insect pest that causes extensive damage to tobacco (Nicotiana tabacum L.) in China. Field trials were conducted in 2008 and 2009 at Longyan in the Fujian Province (China) to evaluate the effects of garlic (Allium sativum L.) as a deterrent to green peach aphids and other arthropods when intercropped in flue‐cured tobacco fields. This study demonstrated that green peach aphids were affected by intercropping garlic in tobacco fields during the 2 yr studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 13 publications
2
42
0
Order By: Relevance
“…Intercropping methods have been used to manipulate pests in many crop fields (Shen et al, 2007;Sohail et al, 2008;Lai et al, 2011;Lai et al, 2017). The successful use of spiders or predators for pest management provides support for the natural enemy hypothesis, which suggests that natural enemies are more abundant and diverse in diversified habitats than in monocultures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intercropping methods have been used to manipulate pests in many crop fields (Shen et al, 2007;Sohail et al, 2008;Lai et al, 2011;Lai et al, 2017). The successful use of spiders or predators for pest management provides support for the natural enemy hypothesis, which suggests that natural enemies are more abundant and diverse in diversified habitats than in monocultures.…”
Section: Discussionmentioning
confidence: 99%
“…White garlic, Allium sativum L., (cultivar) was planted one month before transplanting flue-cured tobacco plants. During the experiment, randomized block design was followed where three blocks and within each, four treatments plots of 12 x 11.2 m were selected as per Lai et al (2011). Each plot was separated from each other by a flue-cured tobacco ridge.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural practices, such as intercropping, and the use of trap crops, barrier crops, companion plants or banker plant systems all enhance vegetation diversity within farmlands and have the potential to contribute to the suppression of agricultural pests (e.g. Smith and McSorley 2000;Ahuja, Rohloff, and Bones 2010;Frank 2010;Mutiga, Gohole, and Auma 2010;Lai, You, Lotz, and Vasseur 2011). In pest management terminology, these cultural practices are known as vegetation management (Landis et al 2000;Huang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Garlic has effectively been incorporated into an intercropping system as a companion crop due to its allelopathic and antimicrobial effects. Some studies have reported that garlic intercropping can prevent insect attack (Mogahed, 2003, Lai et al, 2011 and weed invasion (Mueller et al, 1998). Recent research demonstrated that intercropping with garlic, green garlic (Xiao et al, 2012) and onion (Zhou et al, 2011) can alleviate problems associated with continuous cropping (soil sickness) of cucumbers under protected cultivation.…”
mentioning
confidence: 99%